Young women's genital self-image and effects of exposure to pictures of natural vulvas - Ellen Laan; Daphne K. Martoredjo; Sara Hesselink; Nóinín Snijders; Rik H. W. van Lunsen (Taylor & Francis Group, 2017)
Introduction: Many women have doubts about the normality of the physical appearance of their vulvas. This study measured genital self-image in a convenience sample of college-educated women, and assessed whether exposure to pictures of natural vulvas influenced their genital self-image. Method: Forty-three women were either shown pictures of natural vulvas (N = 29) or pictures of neutral objects (N = 14). Genital self-image was measured before and after exposure to the pictures and two weeks later. Sexual function, sexual distress, self-esteem and trait anxiety were measured to investigate whether these factors influenced genital self-image scores after vulva picture exposure. Results: A majority of the participants felt generally positively about their genitals. Having been exposed to pictures of natural vulvas resulted in an even more positive genital self-image, irrespective of levels of sexual function, sexual distress, self-esteem and trait anxiety. In the women who had seen the vulva pictures, the positive effect on genital self-image was still present after two weeks. Discussion: The results of this study seem to indicate that even in young women with a relatively positive genital self-image, exposure to pictures of a large variety of natural vulvas positively affects genital self-image. This finding may suggest that exposure to pictures of natural vulvas may also lead to a more positive genital self-image in women who consider labiaplasty.